MOOCs and NOOCs in the Training of Future Geography and History Teachers: A Comparative Cross-Sectional Study Based on the TPACK Model - Delfin Ortega-Sanchez; Isabel Maria Gomez-Trigueros (IEEE Access, 2020)
MOOCs (Massive Open Online Courses) and NOOCs (Nano Open Online Courses), which are part of e-learning, are being incorporated into the online teaching strategies of higher education institutions around the world. Research on the outcomes of their implementation has shown both their educational potential and their limitations. However, little is known about the instructional effectiveness of these courses and their potential contribution to the acquisition of specific competencies linked to the TPACK (Technological Pedagogical Content Knowledge) model for the training of future Geography and History teachers. To this end, this study examines perceptions regarding the instructional effectiveness of two MOOCs and two NOOCs on geographical and historical education, through an analysis of the performance in TPACK competency dimensions of future teachers (n = 1993). Based on a cross-sectional descriptive approach, central tendency statistics analyses (mean and standard deviation) and inferential analyses (MannWhitney U test and Wilcoxon rank-sum) were used. Participants reported optimal levels of satisfaction across all competency dimensions of the model for their teacher training. Inferential statistical analyses further revealed the existence of statistically significant differences depending on participants' university and gender. Both the instrument applied and the results obtained are of use in making educational decisions regarding the design and implementation strategies of MOOCs and NOOCs specifically aimed at the professional development of future Geography and History teachers.